please answer this question
Attachments:
![](https://hi-static.z-dn.net/files/d04/e450eb07511d44678426f8cbce55b536.jpg)
Answers
Answered by
14
Step-by-step explanation:
Given -
- a + b + c = 0
To Show :-
- x^a²b-¹c-¹ . x^b²c-¹a-¹ . x^c²a-¹b-¹ = x³
As we know that :-
- a^p . a^q = a^p+q
Now,
➠ x^a²b-¹c-¹ . x^b²c-¹a-¹ . x^c²a-¹b-¹
➠ x^a²-¹-¹ + b²-¹-¹ + c²-¹-¹
➠ x^a^0 + b^0 + c^0 (a^0 = 1)
➠ x^¹+¹+¹
➠ x³
x^a²b-¹c-¹ . x^b²c-¹a-¹ . x^c²a-¹b-¹ = x³
Hence,
LHS = RHS
Attachments:
![](https://hi-static.z-dn.net/files/db6/47bb77583b0f865c432282f1a10bb12b.jpg)
Similar questions